Effect of Oil Palm Fronds and Setaria sp. as Forages Plus Sakura Block on the Performance and Nutrient Digestibility of Kaur Cattle - Jarmuji; Santoso, U.; Brata, B. (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to evaluate the effects of oil palm fronds as a substitute for Setaria sp., on dry matter and organic matter intake, weight gain and nutrient digestibility in Kaur cattle. Methodology: This study used a latin square design that consisted of 4 treatment groups with 4 replicates each. The 4 treatment groups were as follows: (1) Kaur cattle were fed 100% Setaria sp. + sakura block as the control (P0), (2) Kaur cattle were fed 25% oil palm fronds+75% Setaria sp. +sakura block (P1), (3) Kaur cattle were fed 50% oil palm fronds + 50% Setaria sp. + sakura block (P2) and (4) Kaur cattle were fed 75% oil palm fronds+25% Setaria sp. +sakura block. Results: Findings of the study showed that there were significant differences among the treatments (p<0.05) in all observed variables. Dry matter and organic matter intake and weight gains in P2 cattle were significantly higher (p<0.05) than the other treatments. Conclusion: It was concluded that the combination of 50% oil palm fronds and 50% Setaria grass plus sakura block resulted in the best performance of Kaur cattle.